The Effectiveness of Economic Capital and Campaign Strategies in the 2014 and 2020 Soppeng Regional Head Elections - Fadillah, Arfan (Journal of Contemporary Local Politics, 2024)
This study analyzes the results of the regional elections in Soppeng in 2014 and 2020. The results show that economic factors such as the amount of money spent on campaigns are not the only determinants of victory. Non-economic factors such as community support and the relevance of candidates' programs to the needs of the community also have a significant influence. The study compared two pairs of candidates and found that the pair that was closer to the community and had a program that was more in line with the community's needs tended to win, even though they had more limited campaign funds. The findings highlight the importance of community-based campaign strategies, strong support from the community, and relevant programs to win over voters. In addition, this study also concludes that there is a need to improve regulations related to the use of campaign funds, political education for voters, and transparency in campaign finance reporting to strengthen democratic integrity.